Analysis of the Presidential Government Model in Indonesia: Advantages, Disadvantages, and Suitable Alternatives - Susanti, Rani (Social Impact Journal, 2025)
This study examines the presidential model of government implemented in Indonesia, focusing on its advantages and disadvantages in the context of politics and administration. The Indonesian presidential model, in which the president serves as both head of state and head of government, has advantages such as executive stability, clear separation of powers, and strong leadership. However, this model also faces challenges such as the risk of inter-institutional conflict, concentration of power in the president, and lack of parliamentary accountability. To address these shortcomings, this study evaluates several alternative models of government: the British parliamentary model, the Soviet model, and the traditional model. The British parliamentary model offers advantages such as flexibility in the formation and dissolution of government, as well as direct accountability to parliament, although it has the potential for political instability. The Soviet model, with its centralization of power, can increase decision-making efficiency but risks authoritarianism. The traditional model emphasizes local cultural values and is accepted at the community level, but faces challenges in adapting to the modern context. The results of this study indicate that the British parliamentary model is the most suitable alternative to address the shortcomings of Indonesia's presidential system. This model offers a balance between stability and accountability, and allows for better adaptation to the political and social dynamics in Indonesia. The implementation of the parliamentary model can improve government accountability and flexibility, thereby improving effectiveness and responsiveness to the needs of the community. Thus, the adoption of the parliamentary model can be a strategic step to improve governance in Indonesia.